The sociolinguistic policies in the republic of kazakhstan - Sariev, A.; Bimasheva, G. S. (ЗКАТУ им. Жангир хана, 2018)
The article deals with the concept of language policy in modern sociolinguistics. The study is based on the main provisions of the Concept of Language Policy of the Republic of Kazakhstan. Such concepts as "language policy", "language situation", "bilingualism", "multilingualism", "trilingualism" are considered. The following functions of sociolinguistic monitoring are distinguished: analysis and monitoring of the level of knowledge of the state, native and Russian languages of ethnic groups living in Kazakhstan; The role of the state language in the socio-communicative system of Kazakhstan society; public evaluation of measures to implement the status of the state language; character and degree of dominance of the function of language in society; the free choice of the language of communication, learning and creativity; place of the language issue in the migration motivation of the population of Kazakhstan and other countries.Данная статья рассматривает понятие языковой политики в современной социолингвистике. Рассмотрены такие понятия, как «языковая политика», «языковая ситуация», «билингвизм», «многоязычие», «трехъязычие».
"Роль молодежи в развитии науки и инновации в ХХІ веке" в рамках программы "Рухани жаңғыру", посвящ. 20-летию столицы Республики Казахстан - города Астаны "Ел жүрегі - Астана" и 55-летию Западно-Казахстанского аграрно-технического университета имени Жангир хана: мат. третьей респ. науч.-практ. конф. студентов и магистрантов
Keywords: рк; конференции; отечественное издание; республиканская конференция; языкознание; языковая политика; полиязычие